Effect of Collagen Tripeptide and Adjusting for Climate Change on Skin Hydration in Middle-Aged Women: A Randomized, Double-Blind, Placebo-Controlled Trial - Tak, Young Jin; Shin, Dae Keun; Kim, Ae Hyang; Kim, Jun Il; Lee, Ye Li; Ko, Hyun-Chang; Kim, Yong-Woo; Lee, Sang Yeoup (Frontiers in Medicine, 2021)
Introduction: Although collagen is widely used in various forms as a functional ingredient in skin care products, the effect of oral supplementation of collagen tripeptides (CTPs) on human skin is unclear. Moreover, the majority of the positive outcomes of CTP reported so far have not considered the effect of weather conditions. Therefore, we tested the effect of CTP and adjusting for climate change on skin properties in middle-aged women. Materials and Methods: A randomized controlled trial was conducted with 84 women between 40 and 60 years of age. Participants were randomized to receive placebo or 1,000 mg CTP daily for 12 weeks. CTP was prepared from the skin of Nile Tilapia by the digestion method using collagenase from non-pathogenic bacteria of the genus Bacillus. Skin hydration, wrinkling, and elasticity were assessed at baseline and after 6 and 12 weeks with adjustments for temperature, humidity, and ultraviolet A exposure during the evaluation time using weather data from the regional meteorological office. Results: Of the 82 participants, 74 completed the trial without adverse effects. Compared with the control group, trans-epidermal water loss was reduced more in the CTP group after 12 weeks (P < 0.05). At 12 weeks, even after adjustment for humidity, temperature, and UVA in the region, the difference of the two groups in TEWL remained statistically significant (adjusted for humidity and temperature, P = 0.024; adjusted for UVA, P = 0.032; adjusted for temperature, high temperature, and ultraviolet A, P = 0.031). In terms of skin hydration, more improvement was evident in the CTP group than in the control group. In the subgroup analysis, subjects under 50 years of age showed a significant improvement in total score and moisture in the subjective skin improvement questionnaire after taking CTP for 12 weeks. Application of CTP was well-tolerated, and no notable adverse effect was reported from both groups. Discussion: Our findings suggest that oral ingestion of CTP from the Skin of Nile Tilapia (Oreochromis niloticus) is well-tolerated and helps reduce water loss in in middle-aged women. Clinical Trial Registration:www.clinicaltrials.gov/, Identifier: NCT03505684.